Effect of exogenous hydrogen peroxide on biophoton emission from radish root cells - Rastogi, Anshu; Pospísil, Pavel (Plant physiology and biochemistry, 2010)
Biophotons spontaneously emitted from radish root cells were detected using highly sensitive photomultiplier tube. Freshly isolated radish root cells exhibited spontaneous photon emission of about 4 counts s(-1). Addition of hydrogen peroxide to the cells caused significant enhancement in biophoton emission to about 500 counts s(-1). Removal of molecular oxygen using glucose/glucose oxidase system and scavengering of reactive oxygen species by reducing agents such are sodium ascorbate and cysteine completely diminished biophoton emission. Spectral analysis of the hydrogen peroxide-induced biophoton emission indicates that biophotons are emitted mainly in green-red region of the spectra. The data provided by electron paramagnetic resonance spin-trapping technique showed that formation of singlet oxygen observed after addition of H2O2 correlates with enhancement in biophoton emission. These observations provide direct evidence that singlet oxygen is involved in biophoton emission from radish root cells.
Keywords: Luminescence; Spin Trapping; reaktivní formy kyslíku; spin trapping; Reactive Oxygen Species; spektrální analýza; scavengery volných radikálů; Free Radical Scavengers; Oxygen; Electron Spin Resonance Spectroscopy; kyslík; Raphanus; kořeny rostlin; redukční činidla; peroxid vodíku; Photons; Reducing Agents; Spectrum Analysis; Plant Roots; elektronová paramagnetická rezonance; fotony; Hydrogen Peroxide; luminiscence